China dolls : a novel - See, Lisa (Random House, 2014)
"The New York Times bestselling author of Snow Flower and the Secret Fan, Peony In Love, Shanghai Girls, and Dreams of Joy returns with her highly anticipated new novel. A bold and bittersweet story of secrets and sacrifice, love and betrayal, prejudice and passion, China Dolls reveals a rich portrait of female friendship, as three young women navigate the "Chop Suey Circuit"--America's extravagant all-Asian revues of the 1930s and '40s--and endure the attack on Pearl Harbor and the shadow of World War II"--